Exploring Sentence Structure and Grammatical Consistency in AI-Written Essays - Novriyani, Novriyani; Ema Puspitasari, Ema Puspitasari; Puan Alia Haya, Puan Alia Haya; Rizki Anugrah PR, Rizki Anugrah PR (Tarling : Journal of Language Education, 2025)
Artificial intelligence (AI) systems, including tools like ChatGPT and Gemini. Have become increasingly prevalent in the generation of written academic texts, particularly essays. This research focused on sentence sructure and grammatical consistency in essays generated by artifical intelligence (AI) in academic English. The research used descriptive qualitative method to describe how AI constructed sentences and applied grammatical rules in essays. There are five essays were generated by an AI tool using academic prompts, and each was analyzed based on sentence types (simple, compound, complex, and compound-complex) and grammatical consistency (tense usage, subject-verb agreement, and punctuation). The results were expeced to reveal patterns in syntactic construction, highlight strengths and weaknesses in AI-generaed grammar, and provided insights into the reliability of AI for academic writing tasks. The research contributed to discussed in applying linguistics, language education, and using of AI in academic contexts.